2018
DOI: 10.1021/acsnano.8b04869
|View full text |Cite
|
Sign up to set email alerts
|

Ultrathin Bismuth Film on High-Temperature Cuprate Superconductor Bi2Sr2CaCu2O8+δ as a Candidate of a Topological Superconductor

Abstract: One of the key challenges in condensedmatter physics is to establish a topological superconductor that hosts exotic Majorana fermions. Although various heterostructures consisting of conventional BCS (Bardeen−Cooper−Schrieffer) superconductors as well as doped topological insulators were intensively investigated, no conclusive evidence for Majorana fermions has been provided. This is mainly because of their very low superconducting transition temperatures (T c ) and small superconducting-gap magnitude. Here, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
26
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 44 publications
5
26
4
Order By: Relevance
“…We do not observe any leading edge shift of EDCs with temperature, indicating an absence of proximity effect in the present film. This is in sharp contrast to the recent study by Shimamura et al, [24] who have reported a gap opening in the Bi films of similar thickness. We might expect that the thicker the film, the less chance for inducing the pairing at the surface of the film, as the proximity effect is generally limited by the c-axis coherence length.…”
Section: Resultscontrasting
confidence: 99%
See 4 more Smart Citations
“…We do not observe any leading edge shift of EDCs with temperature, indicating an absence of proximity effect in the present film. This is in sharp contrast to the recent study by Shimamura et al, [24] who have reported a gap opening in the Bi films of similar thickness. We might expect that the thicker the film, the less chance for inducing the pairing at the surface of the film, as the proximity effect is generally limited by the c-axis coherence length.…”
Section: Resultscontrasting
confidence: 99%
“…In summary, we have studied the electronic structure of Bi films of various thicknesses on Bi2212. Our results show no evidence of a proximity-induced gap opening in the film-derived states, in contrast to the recent study by Shimamura et al [24] By depositing thinner films and accessing both the substrate and overlayer Bi-states, we discover the fundamental reason for the suppression of proximity effect. Both ARPES and core-level results demonstrate that the Bi deposition modifies the doping level, severely reducing the hole doping and causing the loss of superconductivity at the film-substrate interface.…”
Section: Resultscontrasting
confidence: 99%
See 3 more Smart Citations